2022
DOI: 10.3390/agriculture12122084
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Changes in Vegetable and Field Crops under Drought, Salinity and Weeds Stresses: Control Strategies and Management

Abstract: Weeds are one of the most damaging biotic stresses in crop production, and drought and salinity are considered the most serious abiotic stresses. These factors harmfully affect growth and development in several vegetable and field crops by causing harmful effects on physiological and biochemical characteristics such as water uptake, photosynthesis, relative water content, electrolyte leakage, and antioxidant compounds linked with oxidative stress and the accumulation of reactive oxygen species (ROS). These oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 228 publications
1
18
0
Order By: Relevance
“…The overproduction of ROS, caused by salt stress, can be balanced by antioxidant enzymatic activity [48], which involves several enzymes, such as superoxide dismutase (SOD), peroxidase (POD) and ascorbate peroxidase (APX). Studies have shown that, under saline stress, their activities are increased in salt-tolerant plants, but decreased in saltsensitive ones [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of ROS, caused by salt stress, can be balanced by antioxidant enzymatic activity [48], which involves several enzymes, such as superoxide dismutase (SOD), peroxidase (POD) and ascorbate peroxidase (APX). Studies have shown that, under saline stress, their activities are increased in salt-tolerant plants, but decreased in saltsensitive ones [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of salinity stress on plants encompass various alterations in morphological parameters and biochemical processes. These alterations include reductions in root and shoot length, vegetable production, chlorophyll content, and changes in secondary metabolites such as oxidative compounds, signal molecules, and hormones [ 70 , 71 ]. Salinity adversely affects the germination rate, germination percentage, and growth of seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Salt accumulation in the root zone causes the development of osmotic stress (osmotic effect) and disrupts cell ion homeostasis by inhibiting the uptake of essential nutrients and inducing the accumulation of Na + and Cl − to potentially toxic levels within cells (specific ion effect) [ 62 , 63 ]. These primary stresses induce the generation of reactive oxygen species (ROS) [ 33 , 64 , 65 ], causing a reduction in the activity of certain enzymes [ 33 , 64 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress can contribute to the production of enormous reactive oxygen species (ROS) [ 3 , 21 ]. ROS are known to generate damage to cell membranes and other cellular components [ 31 , 32 , 33 ]. Excessive ROS production leads to lipid peroxidation, enzyme inhibition, and nucleic acid modifications [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%